Post-discharge adherence with venous thromboembolism prophylaxis after orthopedic trauma: Results from a randomized controlled trial of aspirin versus low molecular weight heparin. Issue 4 (April 2018) - Haac, Bryce E.; Van Besien, Richard; O'Hara, Nathan N.; Slobogean, Gerard P.; Manson, Theodore T.; O'Toole, Robert V.; Johal, Herman; Berger, Peter Z.; Reahl, George B.; Marinos, Dimitrius; Degani, Yasmin; Mascarenhas, Daniel; et al.
Abstract : Background: Orthopedic trauma patients are often treated with venous thromboembolism (VTE) chemoprophylaxis with aspirin or low molecular weight heparin (LMWH) after discharge from their index admission, but adherence patterns are not known. We hypothesized that overall adherence would be moderate and greater with aspirin compared to LMWH. Methods: We conducted a randomized controlled trial of adult trauma patients with an operative extremity fracture or any pelvic/acetabular fracture requiring VTE prophylaxis. Patients were randomized to receive either LMWH 30 mg BID or aspirin 81 mg BID. Patients prescribed outpatient prophylaxis were contacted between 10 and 21 days after discharge to assess adherence measured by the validated Morisky Medication Adherence Scale (MMAS-8). Adherence scores were compared between the two treatment arms with similar results for intention-to-treat and as-treated analyses. As-treated multivariable logistic regression was performed to determine factors associated with low-medium adherence scores. Results: One hundred fifty patients (64 on LMWH, 86 on aspirin) on chemoprophylaxis at time of follow-up completed the questionnaire. As-treated analysis showed that adherence was high overall (mean MMAS 7.2 out of 8, SD 1.5) and similar for the two regimens (LMWH: 7.4 vs. aspirin: 7.0, p = 0.13). However, patients on LMWH were more likely to feel hassled by their regimen (23% vs. 9%, p = 0.02). In a multivariable model, low-medium adherence was associated with taking LMWH as the prophylaxis medication (aOR 2.34, CI 1.06–5.18, p = 0.04), having to self-administer the prophylaxis (aOR 4.44, CI 1.45–13.61, p < 0.01), being of male sex (aOR 2.46, CI 1.10–5.49, p = 0.03), and of younger age (aOR 0.72 per additional 10 years of age, CI 0.57–0.91, p < 0.01). Conclusions: Overall post-discharge adherence with VTE prophylaxis was high. Several factors, including prophylaxis by LMWH, were associated with decreased adherence. These factors should be considered when managing patients and designing efficacy trials. Level of Evidence: Therapeutic, level II.